Overview and challenges of citrus industry in Sergipe from 2010 to 2022 - Soares Felix, Ana Gabriela; Docema, Matheus Luís; Almeida de Oliveira Junior, Marcelo (Comunicata Scientiae, 2025)
The Brazilian citrus industry is one of the country's most significant economic and social sectors, positioning Brazil as a global leader in this field. In the state of Sergipe, the citrus industry represents 3% of the Gross Domestic Product (GDP), playing a crucial role in the local economy, with citrus being one of the region's key agricultural products. Given this context, the objective of this study was to analyze the opportunities and challenges faced by Sergipe's citrus sector between 2010 and 2022. The analysis focused on production and commercialization data for sweet oranges, considering climatic, economic, and competitive factors that impact the sector. Data on planted areas, production, crop yield, prices, and rainfall indices were gathered from public research platforms, including the Brazilian Institute of Geography and Statistics (IBGE) and the Agricultural Development Company of Sergipe (EMDAGRO). Throughout the evaluated historical series, there were fluctuations in orange planted areas, with a reduction of 45%, and a 52% decline in fruit production, largely due to climatic conditions and phytosanitary issues. Despite these ongoing challenges, projections suggest a 0.5% increase in orange yield in the coming years. High international demand and changing consumption patterns for both the fruit and its juice, as seen during the COVID-19 pandemic, present an opportunity for local producers, provided that proper crop management practices are implemented to address the existing challenges.